Memaknai Ajaran Alkitab Tentang Keadilan Allah Dari Sudut Pandang Teologi Pentakosta - Kosma Manurung (Institut Agama Kristen Negeri Palangka Raya, 2021)
Human social identity requires him to continue to be connected with other humans in a harmonious social relationship. The Bible also places justice as a vital part of human social life. The biblical description reveals that God is a just person and there is never fraud in God. The aim of this research is to interpret the Bible's teachings about God's justice from the perspective of Pentecostal theology. This article contains an explanation of the importance of justice for humans, the Bible's narrative about God's justice, and the way Pentecostals interpret God's justice. The method used in this research is descriptive and literature review. Based on the results of the discussion, it was concluded that in the view of the Pentecostals, God's justice speaks of God's character. The justice of Allah is also interpreted by the Pentecostals as God's Rule that God wants to be obeyed. In addition, God's justice also means the defense of Allah and the demands that God wants every believer to do in social life so that they can be maximized as witnesses of God and become salt and light for the community where God has placed. Identitas sosial manusia menuntutnya untuk terus terkoneksi dengan manusia lainnya dalam sebuah hubungan sosial yang harmonis. Alkitab pun meletakkan keadilan sebagai bagian vital dalam kehidupan sosial manusia. Deskripsi Alkitab mengungkapkan bahwa Allah adalah pribadi yang adil dan tidak ada kecurangan dalam diri Allah. Tujuan penelitin ini bermaksud memaknai ajaran Alkitab tentang keadilan Allah dari sudut pandang teologi Pentakosta. Artikel ini berisi tentang penjelasan pentingnya keadilan bagi manusia, narasi Alkiab tentang keadilan Allah, dan cara kaum Pentakosta memaknai keadilan Allah. Metode yang digunakan dalam penelitian ini deskriptif dan kajian literatur. Berdasarkan hasil pembahasan ditarik kesimpulan bahwa dalam pandangan kaum Pentkosta keadilan Allah berbicara karakter Allah. Keadilan Allah juga dimaknai kaum Pentaksota sebagai Aturan Allah yang Allah ingin untuk dipatuhi. Selain itu, keadilan Allah juga dimaknai pembelaan Allah dan tuntutan yang Allah ingin setiap orang percaya lakukan dalam kehidupan bermasyarakat agar bisa maksimal sebagai saksi Tuhan dan menjadi garam serta terang bagi komunitas dimana Tuhan tempatkan.